Survival and transfer of Escherichia coli to fresh produce from organically managed soils amended with poultry litter - McKenzie-Reynolds, Petrina; Millner, Patricia; Hashem, Fawzy; Marsh, Lurline; Smith, Brett; Kenney, Annette; Allen, Arthur; Parveen, Salina; Collick, Amy S. (Frontiers in Sustainable Food Systems, 2025)
IntroductionPoultry litter (PL) compost and heat-treated PL-pellets (PP) are common organic fertilizer/soil amendments in specialty crop production and soil health management. However, such products may enhance survival and persistence of foodborne pathogens and their transfer to fresh produce.MethodsA replicated (n = 4) 2-year, randomized complete block field-plot inoculated-challenge study, with PL treatments (composted APL and PP) and cover crop/soil placement, was conducted to assess soil persistence/transfer of generic gE.colirif-R to cantaloupe, cucumber, spinach, and table radish, in cover-cropped USDA-National Organic Program (NOP) 8-years managed as certified plots. Amended soils were analyzed monthly for E. coli up through 90-120-day NOP required wait periods between PL application and produce harvest. Cantaloupe, cucumber, spinach, and table radish, grown compliant with NOP standards, were assayed at harvest for pathogens (Salmonella, Listeria monocytogenes, Staphylococcus aureus) and gE. coli.Results and discussionAll amended, inoculated soils were positive for the inoculated E. coli (6-log MPN/g) immediately after inoculation. At 90 dpi, all plot soils were positive for the inoculated gEcrif-R; by 120 dpi, gEcrif-R concentrations in soils declined significantly (p < 0.05) both in 2018 and 2019. No other pathogens (Salmonella, Listeria monocytogenes, Staphylococcus aureus) were detected at 0 or 90 dpi in plot soils. Generic Ecrif-R was detected on four of 16 cantaloupes, four of 16 cucumbers from APL plots; four of 20 radish bulbs from till incorporated and four from subsurface-applied APL tested positive for gEcrif-R at 90 dpi. By 120 dpi, only two spinach plants (n = 20) were positive from subsurface APL plots; no other pathogens or gEcrif-R were recovered for any crops in 2018–2019. Significant, consistent declines and decreasing survival throughout the growing seasons in populations of inoculated E. coli in soil, resulted in very low detection on any unwashed produce by 90 and 100 dpi in accord with NOP manure amendment-to-harvest wait times. Exposure to a combination of environmental conditions, including soil moisture, splash transfer of soil to produce, and temperatures (soil and air), impact E. coli populations in tilled and subsurface PL product-amended soils and on produce managed in compliance with organic production requirements.